Peculiarities of Molecular Hydrogen Behavior in Palladium Nanopores of Different Morphology; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Korchuganov A. V.; Zolnikov K. P.; Kryzhevich D. S.; Psakhie S. G. Sergey Grigorievich (2016, 2016)
Title screen